Development and Validation of New HPLC Method for the Determination of Imidazolidinyl Urea in Topical Formulation - Kızılçay, Gamze Ergin; Toker, Sıdıka Ertürk; Matur, Dilek (Current Pharmaceutical Analysis, 2024)
Introduction In this study, a new, simple, selective, and fast liquid chromatographic method has been developed and validated for the determination of imidazolidinyl urea used as an anti-microbial agent in topical formulation. Methods The developed HPLC method using a diode array detector for the determination of imidazolidinyl urea was applied to the topical formulation. Imidazolidinyl urea in the sample was analyzed in the cyano column (250 x 4,6 mm, 5 µm i.d.) under chromatographic conditions, where the flow rate was determined as 1.0 mL/min. The column oven was 40.0°C, and imidazolidinyl urea was detected at 210 nm. Isocratic application of acetonitrile-water (25:75, v/v) was used as the mobile phase system. The validation of the developed method was performed according to the International Conference on Harmonisation guidelines Q2 (R1). Results The linearity range of the imidazolidinyl urea was 0.050-0.150 mg/mL, and the limits of detection and quantification were calculated to be 62.5x10-6 mg/mL and 125x10-6 mg/mL, respectively. Assay recovery and precision of imidazolidinyl urea from topical formulation at 0.050, 0.100, and 0.125 mg/mL concentrations were evaluated. The mean recoveries for imidazolidinyl urea in the topical formulation were calculated as 98.857-104.560%. Conclusion The validated method was successfully applied to the determination of imidazolidinyl urea in a topical formulation. The proposed method is reproducible and reliable and can be used safely for routine analysis.
Keywords: HPLC